Assessment of cell mediated immune response in spontaneously occurring canine mammary gland tumours by leucocytemiggration inhibition test (LMIT) - Lonkar, P. S. (2021)
In the present study, cell mediated immune response in the mammary gland tumour-bearing bitches was studied by evaluating functional capacity of sensitised lymphocytes using Leucocyte Migration Inhibition Test (LMIT). Cell membrane antigens (allogenic type) of different molecular weights separated from mammary gland tumour tissue were subjected to LMIT against leucocytes separated from twenty tumour-bearing bitches and six apparently healthy dogs used as control group. Statistically, the tumour bearing dogs had significantly lower migration index values in comparison to healthy control dogs. Thus, leucocytes separated fom tumour-bearing animals showed positive LMIT response while there was normal migration in the healthy control dogs. It is seen that the functional capacity of T Lymphocytes in the mammary gland tumour-bearing bitches played a major role in cellular immunity and was not affected as indicated by migration inhibition index.